Follicular T helper cells and humoral reactivity in kidney transplant patients. (May 2015) - de Graav, G. N.; Dieterich, M.; Hesselink, D. A.; Boer, K.; Clahsen‐van Groningen, M. C.; Kraaijeveld, R.; Litjens, N. H. R.; Bouamar, R.; Vanderlocht, J.; Tilanus, M.; Houba, I.; Boonstra, A.; et al.
Summary Memory B cells play a pivotal role in alloreactivity in kidney transplantation. Follicular T helper (Tfh) cells play an important role in the differentiation of B cells into immunoglobulin‐producing plasmablasts [through interleukin (IL)‐21]. It is unclear to what extent this T cell subset regulates humoral alloreactivity in kidney transplant patients, therefore we investigated the absolute numbers and function of peripheral Tfh cells (CD4POSCXCR5POS T cells) in patients before and after transplantation. In addition, we studied their relationship with the presence of donor‐specific anti‐human leucocyte antigen (HLA) antibodies (DSA), and the presence of Tfh cells in rejection biopsies. After transplantation peripheral Tfh cell numbers remained stable, while their IL‐21‐producing capacity decreased under immunosuppression. When isolated after transplantation, peripheral Tfh cells still had the capacity to induce B cell differentiation and immunoglobulin production, which could be inhibited by an IL‐21‐receptor‐antagonist. After transplantation the quantity of Tfh cells was the highest in patients with pre‐existent DSA. In kidney biopsies taken during rejection, Tfh cells co‐localized with B cells and immunoglobulins in follicular‐like structures. Our data on Tfh cells in kidney transplantation demonstrate that Tfh cells may mediate humoral alloreactivity, which is also seen in the immunosuppressed milieu.